A new species of genus Thymioptila Diakonoff (Lepidoptera: Tortricidae) from Thailand and a new record, Thymiotila oedalea (Meyrick, 1909), from Laos - Pinkaew, Nantasak (Zootaxa, 2022)
A new species, Thymioptila clavata Pinkaew sp. nov., is described based on three male specimens collected from Thailand. Thymioptila oedalea (Meyrick) is recorded for the first time from Laos. Raised scale tuft on forewing and dorsoapical claviform process of cucullus are the unique characters for the genus. The illustrations of adults and genitalia of both species are provided. The new taxon increases the number of described Thymioptila species to two.